Mafia Tanah dan Sistem Peradilan di Indonesia: Studi Kasus Tuduhan Pemalsuan Dokumen terhadap Advokat studi putusan PN Bekasi Nomor 484/Pid.B/2023/PN Bks (Lembaga Pengembangan Kinerja Dosen, 2025)
Land disputes in Indonesia often involve organized land mafia practices that exploit weaknesses in the administrative system and collude with corrupt officials. The land dispute case in Bekasi involving advocate Dani Bahdani exemplifies how allegations of document forgery can lead to the criminalization of legal professionals within the context of land mafia activities. This study analyzes the role of advocates in facing such allegations and evaluates the effectiveness of law enforcement against land mafia practices involving corrupt officials and judicial mafia. A normative juridical method with a case study approach based on court decisions is used to examine this phenomenon. The study findings highlight the crucial role of advocates as defenders of justice while revealing ongoing challenges in effective law enforcement. Recommendations focus on strengthening the integrity of officials, protecting advocates, and enhancing transparency in land administration to realize justice in Indonesia’s land law system.